Penyuluhan Fisioterapi Mengenai Baby Massage dan Oral Motor Exercise untuk Peningkatan Nafsu Makan Pada Kelas Balita di RW 03 kelurahan Arjosari, Kota Malang - Syamsa Liatis Zailia; Nungki Marlian Yuliadarwati; Fika Ertitri (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Introduction: One form of health service that physiotherapy can provide is using communication and education to the community, such as education in the toddler posyandu community. Methods: the method used is the provision of health promotion counseling on baby massage and oral motor exercise in infants to toddlers. This counseling was conducted on October 14, 2024 in the toddler class RW 03, Arjosari village, Blimbing District, Malang City with 10 mothers of toddlers being targeted in this counseling. The implementation of this counseling uses leaflets as promotional media. Giving pre-test and post-test as an instrument to measure the effectiveness of this counseling. Results: the results showed that the second question of the pre-test obtained a value of 0% and the post-test value obtained a result that increased to 90%. Then, for the third question, the pre-test score was 0% and the post-test score increased to 70%. Conclusion: The evaluation results state that the counseling activities carried out in the toddler class have increased knowledge to participants regarding oral motor exercise and baby massage.